2017
DOI: 10.1155/2017/2717848
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Properties of PVC/Bamboo Composites under Static and Dynamic-Thermal Conditions: Effects of Composition and Water Absorption

Abstract: Polyvinyl chloride (PVC)/bamboo composites have been prepared and assessed for their use in interior and exterior loadbearing applications. PVC composites were formed by compounding PVC with different bamboo particle sizes and loadings. The mechanical properties of these composites were determined at both ambient and elevated temperatures and after long-term water soaking. Analysis revealed that bamboo incorporation improved the PVC composite flexural modulus which was also observed with dynamic mechanical-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…PVC in this study not only serves as a composite binder, but also offers enhanced material performance in term of stiffness, strength and thermal stability, as described previously. 41 In the fabricated electrode, PVC acts as a composite binder that holds C and Chi particles together (Fig. 3) to form a mechanically and chemically stable electrode.…”
Section: Resultsmentioning
confidence: 99%
“…PVC in this study not only serves as a composite binder, but also offers enhanced material performance in term of stiffness, strength and thermal stability, as described previously. 41 In the fabricated electrode, PVC acts as a composite binder that holds C and Chi particles together (Fig. 3) to form a mechanically and chemically stable electrode.…”
Section: Resultsmentioning
confidence: 99%
“…PVC has been widely used as a polymer matrix in composite due to its various features such as easy molding, good mechanical properties, high hardness and excellent fire resistance. 39,40 The incorporation of materials based on natural recourses generally enhances biodegradability but deteriorates the other properties. 41,42 A judicial blend of natural and synthetic material may improve the overall properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Jamil et al [2] revealed that tensile modulus and Shore hardness increased with rice husk loadings in the TPNR matrix, and the addition of kenaf fiber in the TPNR matrix had significantly increased the tensile, flexural, and impact properties [5]. Further, the natural fibers also offer many advantages such as low cost, high toughness, lightweight, less abrasive on processing tools, and low energy consumption in manufacturing [6,7].…”
Section: Introductionmentioning
confidence: 99%